Coronavirus disease 19 and risk of hyperglycemia among Iraqi patients - Ali H. Ad’hiah (SpringerOpen, 2021)
Abstract A cross-sectional observational study was conducted on 213 patients with COVID-19 who did not have a clinical history of diabetes at hospital admission. One week after hospitalization, they were stratified by random blood glucose levels. It was found that 25.4, 22.5 and 52.1% of COVID-19 patients were classified as normoglycemia, prediabetes and diabetes, respectively. The study indicated that diabetes may be a risk factor for COVID-19 or the disease may be associated with an increased risk of developing diabetes.